Sex differences in health-related quality of life among acute myocardial infarction survivors: an inverse weighted propensity score analysis. (25th November 2020) - Dondo, T; Munyombwe, T; Hall, M; Hurdus, B; Oliver, G; Gale, C.P
Abstract: Background: Over 800, 000 women in the UK are living with coronary heart disease, which is the main cause of acute myocardial infarction (AMI). Marked improvements have been noted in clinical outcomes following AMI due to improved use of evidence-based treatments. However, sex differences in outcomes following AMI persist, with limited evidence in the literature concerning patient reported outcomes such as health related quality of life (HRQoL). Purpose: To investigate sex differences in HRQoL following AMI. Methods: Data on HRQoL among 9, 566 survivors of AMI were collected from 77 National Health Service hospitals in England between 1 November 2011 and 24 June 2015. HRQoL at time of hospitalisation with an AMI as well as at 1, 6 and 12 months post discharge were collected using the self-reported EuroQol five dimension questionnaire which contains a descriptive system (EQ-5D ranging from −0.5 "worse than death" to 1 "full health") and a visual analogue scale (EQ-VAS ranging from 0 "worst imaginable health state" to 100 "best imaginable health state"). Multilevel regression modelling coupled with inverse probability weighting propensity score analysis was used to investigate longitudinal trajectories of sex differences in perceived HRQoL following AMI. Results: Overall, there were 2, 397 (25%) women in the study. HRQoL improved over time, however, women had a lower baseline HRQoL compared with men (EQ-VAS mean (SD) 59.8 (20.4) vs. 64.5 (20.9), and EQ-5D median (IQR) 0.73 (0.52 to 0.88) vs. 0.81 (0.62 to 1.00). Sex differences in HRQoL over time persisted, with women having a reduced HRQoL (EQ-VAS coefficient: −4.41, 95% CI: −5.16 to −3.66 and EQ-5D coefficient: −0.07, −0.08 to −0.06) and across the individual EQ-5D dimensions women were more likely to report problems with anxiety (odds ratio 2.03, 95% CI: 1.80 to 2.29), mobility (1.82, 1.58 to 2.09), self-care (1.75, 1.47 to 2.08), usual activities (1.70, 1.52 to 1.89) and pain (1.59, 1.45 to 1.75). Conclusion: Although quality of life improves for AMI survivors, women have a lower baseline and worse recovery compared with men. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation, Wellcome Trust, Sir Henry Wellcome Postdoctoral Fellowship